2020
DOI: 10.1371/journal.pone.0232364
|View full text |Cite
|
Sign up to set email alerts
|

Induced abortion incidence and safety in Côte d’Ivoire

Abstract: Background In Cô te d'Ivoire, induced abortion is legally restricted unless a pregnancy threatens a woman's life. Yet the limited available evidence suggests abortion is common and that unsafe abortion is contributing to the country's high maternal mortality. Our study aimed to estimate the one-year incidence of induced abortion in Cô te d'Ivoire using both direct and indirect methodologies, determine the safety of reported abortions, and identify the women most likely to experience a recent induced abortion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 15 publications
4
46
0
1
Order By: Relevance
“…Other recent survey data from Nigeria, Côte d'Ivoire, and India also suggest this behavior is common. Interviewers asked women if they had ever done something to remove a pregnancy at a time when they could not or did not want to be pregnant followed by a question about whether they had ever done something to bring back their menses when they were worried they were pregnant (Bell et al 2020a;Bell et al 2020b;Ahmad et al 2020). Investigators captured significant rates of menstrual regulation among women who reported "no" to the prior question about ever ending a pregnancy.…”
Section: Ambiguity In Action: Menstrual Regularitymentioning
confidence: 99%
“…Other recent survey data from Nigeria, Côte d'Ivoire, and India also suggest this behavior is common. Interviewers asked women if they had ever done something to remove a pregnancy at a time when they could not or did not want to be pregnant followed by a question about whether they had ever done something to bring back their menses when they were worried they were pregnant (Bell et al 2020a;Bell et al 2020b;Ahmad et al 2020). Investigators captured significant rates of menstrual regulation among women who reported "no" to the prior question about ever ending a pregnancy.…”
Section: Ambiguity In Action: Menstrual Regularitymentioning
confidence: 99%
“…Biases introduced by respondents reporting zero confidantes have been documented in other social network-based incidence studies, including the problem of the "zero female respondent" in the Sibling Method (Gakidou & King, 2006;Masquelier, 2013). Gakidou and King (2006) proposed a weighting adjustment to correct for this problem in measuring mortality, which has been adapted by other Confidante Method studies Bell, Sheehy, et al, 2020;Keogh et al, 2020).…”
Section: Evaluation Of Assumptions Associated With the Denominatormentioning
confidence: 99%
“…Given the fact that this imputation approach requires two substantial assumptions that are not supported by the available data, it seemed untenable to produce estimates when a large portion of the data was imputed and not observed. Other studies using this adjustment technique have imputed even larger proportions of their data, ranging from one-third in Ghana (Keogh et al, 2020) to over 50% in Nigeria Bell, Sheehy, et al, 2020), and interpretations of the resulting incidence estimates should be made with caution.…”
Section: Evaluation Of Assumptions Associated With the Denominatormentioning
confidence: 99%
See 1 more Smart Citation
“…Data regarding TOP in LMICs is predominantly generated from health facility data and household surveys, notably Demographic and Health Surveys (DHS), plus special Maternal Health Surveys [11]. Other studies have employed different methods to collect information on TOP such as the confidante method, the list experiment, the abortion incidence method (AICM), and the modified AICM [12][13][14].…”
Section: Introductionmentioning
confidence: 99%